2005
DOI: 10.2741/1691
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic excitotoxicity in sepsis: pro-inflammatory priming of macrophages by norepinephrine

Abstract: In the history of medicine, the interaction between mind and body has been repeatedly proposed. However, the influence of the nervous system on the immune regulation has, until now, drawn little attention. In this regard, the adrenergic system has been explored, and mainly catecholamine-mediated anti-inflammatory effects have been described. These inhibitory effects of epinephrine and norepinephrine were found to be mediated by beta2-adrenoceptors expressed on mononuclear cells. Recently, the role of the paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 78 publications
3
48
0
3
Order By: Relevance
“…It is now widely accepted that the nervous system reflexively regulates the inflammatory response in real time (44,45). Our previous studies have indicated that the release of the sympathetic neurotransmitter, norepinephrine (NE), from the small intestine is increased in sepsis, and that NE potentiates endotoxin-induced TNF-α upregulation via the A subtype of α 2 -adrenoceptors expressed on the surface of Kupffer cells (44). Ghrelin has sympathoinhibitory properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now widely accepted that the nervous system reflexively regulates the inflammatory response in real time (44,45). Our previous studies have indicated that the release of the sympathetic neurotransmitter, norepinephrine (NE), from the small intestine is increased in sepsis, and that NE potentiates endotoxin-induced TNF-α upregulation via the A subtype of α 2 -adrenoceptors expressed on the surface of Kupffer cells (44). Ghrelin has sympathoinhibitory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ghrelin activates the vagus nerve and vagal blockade abolishes ghrelin-induced feeding and growth hormone secretion (49). Stimulation of the vagus nerve can attenuate systemic inflammatory responses rapidly through inhibiting the activation of macrophages and endothelial cells (44,45). Our previous studies have shown that the antiinflammatory effect of ghrelin requires the intact vagus nerve, as vagotomy prevents its beneficial effects in sepsis and gut ischemia reperfusion injury (18,50).…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic excitotoxicity entails neurogenic priming of the systemic proinflammatory response. PTSD-associated SNS arousal may also activate the RAAS and promote inflammatory pathways [80]. …”
Section: Ptsd-related Risk Factors For Cardiometabolic Diseasementioning
confidence: 99%
“…Subsequently, lymphopenia with a mismatch between T helper and T cytotoxic lymphocytes with sustained neutrophil activity [55] develops. Released proinflammatory cytokines, in turn, can influence central noradrenergic pathways [56]. Overall, norepinephrine interferes with immunocompetence [57] which could contribute to evolving multiorgan failure [58] (Figures 4a, 4b, and 4d).…”
Section: Differential Influence Of Norepinephrinementioning
confidence: 99%
“…In addition, b-adrenergic activation controls release of pro-and antiinflammatory cytokines [44,65,66] and contributes to depressed cellmediated inflammation by stimulating the peroxisome proliferator-activated receptor gamma (PPARgamma), a nuclear hormone receptor that mediates antiinflammatory actions [67], as well as inhibiting NF-kB and activating I-kBa [68,69]. At low norepinephrine concentrations (»20 nM), a 2 receptor activation stimulates TNF-a and IL-1b production in hepatic Kupffer cells which is inhibited by high concentrations via b 2 -adrenergic receptors [56]. b 2 -adrenergic stimulation also induces cellular immunosuppression by downregulating various receptors on stimulated human peripheral blood mononuclear cells [70].…”
Section: Differential Influence Of Norepinephrinementioning
confidence: 99%